Identification Identification of Work Accidents at PT. Plantation Nusantara IV Using the Job Safety Analysis Method: Identification of Work Accidents at PT. Plantation Nusantara IV Using the Job Safety Analysis Method - Reza Adrian Purnawan; Diana Khairani Sofyan (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The development of industry in Indonesia is currently taking place very rapidly along with the advancement of science and technology. The development of science and technology has made the use of production tools increasingly complex. Every year there are more than 250 workplace accidents and more than 160 million workers become ill due to workplace hazards. Based on the results of a preliminary survey at PKS PTPN IV Air Batu, by conducting observations, literature studies and interviews with employees, it is known that there were 17 work accidents based on the recapitulation data of work accidents for the 2023 period. Based on this description, the researcher chose the Job Safety Analysis method.The work station in the boiler factory area is the part that has the most potential for accidents based on the analysis of potential accident risks that occur and requires serious treatment and mitigation measures. The potential hazards include burns, gas poisoning, boiler explosions due to component failure, noise, burning by residual steam, slipping due to slippery work floors. This is because workers are very close to hot objects from the boiler, the combustion of the boiler's fuel shell and the slippery work floor. The hazard controls carried out include workers being required to use complete PPE, good ventilation, routine inspection of safety valves, periodic pressure monitoring, routine maintenance, limiting maximum pressure, preventive maintenance, sound insulation, cooling the boiler gradually, using non-slip footwear, waiting until the boiler is completely cool, using complete APD